Liquid exfoliated graphene smart layer for structural health monitoring of composites. (July 2017) - Jan, Rahim; Habib, Amir; Khan, Zaffar M; Khan, Muhammad Bilal; Anas, Muhammad; Nasir, Ali; Nauman, Saad
Graphene nanosheets were exfoliated from graphite using liquid exfoliation method. Smart sensing layer was prepared by dispersing graphene nanosheets in thermoplastic polyurethane. The smart sensing layers thus obtained were pasted on to the glass fiber laminated composite specimens. The sensing layer due to its piezoresistivity was employed for detecting strains in the composite specimens. The results show that the smart sensing layer can be employed for strain sensing in the composite structures. The results hold promise for various applications of these sensors for structural health monitoring in composite parts.